Unjuk Kerja Destilasi Air Energi Surya - I Gusti Ketut Puja; FA. Rusdi Rusdi Sambada (Jurnal Energi Dan Manufaktur, 2012)
Clean water is daily needs for society, especially for drinking and cooking. Existing water sources oftenalready contaminated with dirt, salt (sea water), heavy metals, bacteria or other harmful materials. Thewater in this condition can be detrimental to health if used for drinking or cooking, hence the water has tobe rarefied first. There are many ways to purify contaminated water, one way is by distillation. Distillationprocess requires heat to evaporate the contaminated water before condensed and produce clean water.Thermal energy for distillation process can come from many sources, one of which is solar energy. Thepurpose of this study is to investigate the performance difference between solar powered water distillationthat uses parabolic collector and reflector with solar powered water distillation without the use of paraboliccollector and reflector (basic form). Distillated water will be tested in the laboratory to determine whetherthe water quality qualifies as drinking water or not after distillation process. Equipment which used in thisstudy consisted of contaminated water tanks, distillation apparatus and distillated water storage. Distillationapparatus has a length of 1 meter and 0.5 meters wide. There are three variations on the distillationapparatus used i.e. distillation with reflector, distillation with parabolic collector and distillation withoutreflector and collector (basic form). Distillation appliance is equipped with water depth indicator. Waterdepth inside the distillation varied i.e. 5 mm, 7.5 mm, and 10 mm. The results showed a maximum ofdistilled water produced is 0.850 liter in 2 hours with an average efficiency of 49.2% produced by thedistillation using reflector with 5 mm water depth. Maximum of distilled water yield with 10 mm water depthis 0.20 liter in 2 hours produced by distillation using parabolic collectors. Laboratory test stated that qualityof distilled water can be accepted as drinking water.